2019
DOI: 10.3390/pr7120896
|View full text |Cite
|
Sign up to set email alerts
|

Game Analysis of Wind Storage Joint Ventures Participation in Power Market Based on a Double-Layer Stochastic Optimization Model

Abstract: The volatility of a new energy output leads to bidding bias when participating in the power market competition. A pumped storage power station is an ideal method of stabilizing new energy volatility. Therefore, wind power suppliers and pumped storage power stations first form wind storage joint ventures to participate in power market competition. At the same time, middlemen are introduced, constructing an upper-level game model (considering power producers and wind storage joint ventures) that forms equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…(2) Outer game: each power supplier constitutes a competitive non-cooperative game among themselves, and reaches bilateral transactions with large consumers through bidding strategies [18]; each power supplier strives to make its own bidding competitive among the biddings of multiple power suppliers in order to obtain more electricity purchases from large consumers and maximize its profit from the sale of electricity [19]. (2) Outer game: each power supplier constitutes a competitive non-cooperative game among themselves, and reaches bilateral transactions with large consumers through bidding strategies [18]; each power supplier strives to make its own bidding competitive among the biddings of multiple power suppliers in order to obtain more electricity purchases from large consumers and maximize its profit from the sale of electricity [19].…”
Section: Construction Of Double Game Model For Direct Purchase Of Ele...mentioning
confidence: 99%
“…(2) Outer game: each power supplier constitutes a competitive non-cooperative game among themselves, and reaches bilateral transactions with large consumers through bidding strategies [18]; each power supplier strives to make its own bidding competitive among the biddings of multiple power suppliers in order to obtain more electricity purchases from large consumers and maximize its profit from the sale of electricity [19]. (2) Outer game: each power supplier constitutes a competitive non-cooperative game among themselves, and reaches bilateral transactions with large consumers through bidding strategies [18]; each power supplier strives to make its own bidding competitive among the biddings of multiple power suppliers in order to obtain more electricity purchases from large consumers and maximize its profit from the sale of electricity [19].…”
Section: Construction Of Double Game Model For Direct Purchase Of Ele...mentioning
confidence: 99%
“…Zhang et al [24] proposed that the optimization of pumped storage capacity price mechanism could effectively improve the utilization rate of renewable energy. Based on the doublelayer stochastic optimization model and the assumed samples, Ma et al [25] posited a competitive equilibrium pricing mechanism for wind power suppliers, pumped storage plants and intermediate vendors. Given the parameters of the storage system, the case study of Li et al [26] also suggested that adopting a joint pricing mechanism of "wind + pumped storage" would help to improve the efficiency of the storage system.…”
Section: The Efficiency Of Energy Storage Industrymentioning
confidence: 99%
“…Many studies found that multi-level cooperative planning and control of energy storage systema reduced the investment cost of the system and realized the optimal configuration operation of energy storage equipment [19,20]. Wu et al [21] provided joint participation of multiple wind power and pumped storage power plants in a spot market model, which considered the uncertainty of wind power real-time output, and proposed an optimal bidding strategy before a joint wind storage day. Heussen et al [22] designed operating strategies for up to 100% RES power systems, explicitly considering non-dispatchable generation and storage capacity, as well as the evaluation of operational performance in terms of energy efficiency, reliability, environmental impact, and cost.…”
Section: Introductionmentioning
confidence: 99%